2015
DOI: 10.1210/me.2014-1251
|View full text |Cite
|
Sign up to set email alerts
|

RXR Agonist Modulates TR: Corepressor Dissociation Upon 9-cis Retinoic Acid Treatment

Abstract: Transcriptional regulation controlled by thyroid hormone receptor (TR) drives events such as development, differentiation, and metabolism. TRs may act either as homodimers or as heterodimers with retinoid X receptor (RXR). Thyroid hormone T3 preferentially binds TR-RXR heterodimers, which activate transcription through coactivator recruitment. However, it is unclear whether TR-RXR heterodimers may also be responsive to the canonical RXR agonist 9-cis retinoic acid (9C) in the context of physiological gene regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 82 publications
1
12
0
3
Order By: Relevance
“…An important principle is that heterodimerization not only yields factors with different affinities for DNA, but also combines activators from different groups, which carry DBDs of different affinities and have ADs of different properties. For example, the thyroid hormone nuclear receptor (TR) can form a TR/TR pair and a pair with the retinoid X-receptor, TR/RXR, which binds DNA more strongly than TR/TR [ 195 , 196 ]. Dimerization of MyoD (see below) with the ubiquitously expressed protein E12 or E47 is required for its maximal DNA-binding activity [ 197 , 198 ].…”
Section: Mechanisms Of Transcription Activation In Eukaryotesmentioning
confidence: 99%
“…An important principle is that heterodimerization not only yields factors with different affinities for DNA, but also combines activators from different groups, which carry DBDs of different affinities and have ADs of different properties. For example, the thyroid hormone nuclear receptor (TR) can form a TR/TR pair and a pair with the retinoid X-receptor, TR/RXR, which binds DNA more strongly than TR/TR [ 195 , 196 ]. Dimerization of MyoD (see below) with the ubiquitously expressed protein E12 or E47 is required for its maximal DNA-binding activity [ 197 , 198 ].…”
Section: Mechanisms Of Transcription Activation In Eukaryotesmentioning
confidence: 99%
“…However, Rxrb has two subtypes, Rxrba and Rxrbb, and Rxrba has several variants. A literature review revealed that little information is available on specific RXR with TR heterodimerization (Leid et al, 1992;Nagpal et al, 1993;Germain et al, 2006;Fattori et al, 2015). Therefore, we cloned LBDs from both zebrafish Rxrba-and Rxrbb.…”
Section: Discussionmentioning
confidence: 99%
“…Three independent experiments were performed. Besides, to evaluate if the mutation in ADAM17cyto was able to change its secondary structure, circular dichroism analysis was performed with both proteins (ADAM17cytoWT and ADAM17cytoF730A) as previously described [ 49 ]. One independent experiment was performed.…”
Section: Methodsmentioning
confidence: 99%